2008
DOI: 10.1111/j.1365-2419.2008.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and spawning dynamics of capelin (Mallotus villosus) in Glacier Bay, Alaska: a cold water refugium

Abstract: Pacific capelin (Mallotus villosus) populations declined dramatically in the Northeastern Pacific following ocean warming after the regime shift of 1977, but little is known about the cause of the decline or the functional relationships between capelin and their environment. We assessed the distribution and abundance of spawning, non-spawning adult and larval capelin in Glacier Bay, an estuarine fjord system in southeastern Alaska. We used principal components analysis to analyze midwater trawl and beach seine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
0
35
1
Order By: Relevance
“…In Alaska, a signature change in fish and shellfish communities following the 1977 regime shift was the virtual disappearance of shrimp and capelin in nearshore trawl surveys (Anderson et al 1997, Anderson & Piatt 1999. Whether the change in capelin stocks was manifested primarily in overall abundance, distributional shifts, or both is poorly understood (Brown 2002, Doyle et al 2002, Arimitsu et al 2008. Certainly, pockets of local capelin abundance (as reflected in seabird diets) persisted in the 1980s (Hatch & Sanger 1992), but limited information on diets prior to 1977 suggests greater use of capelin during the preceding cold period in Alaska (Piatt & Anderson 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In Alaska, a signature change in fish and shellfish communities following the 1977 regime shift was the virtual disappearance of shrimp and capelin in nearshore trawl surveys (Anderson et al 1997, Anderson & Piatt 1999. Whether the change in capelin stocks was manifested primarily in overall abundance, distributional shifts, or both is poorly understood (Brown 2002, Doyle et al 2002, Arimitsu et al 2008. Certainly, pockets of local capelin abundance (as reflected in seabird diets) persisted in the 1980s (Hatch & Sanger 1992), but limited information on diets prior to 1977 suggests greater use of capelin during the preceding cold period in Alaska (Piatt & Anderson 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct oceanographic and circulation patterns [36], [37], as a result of rapid and repeated advances and retreats of tidewater glaciers over the past 225 years [38][40], have resulted in sustained levels of mixing, high levels of primary productivity, and abundant communities of forage fish [41], [42]. Johns Hopkins Inlet (58° 50.896' N, −137° 6.121' W), an expansive (12 km long × 2.5 km wide) tidewater glacial fjord in the upper West Arm of Glacier Bay (Figure 1), was chosen as the capture location for seals because the inlet hosts the largest aggregation of seals (>2,000) in Glacier Bay during the summer months and represents one of the primary glacial ice pupping sites for harbor seals in Alaska [29], [30], [43].…”
Section: Methodsmentioning
confidence: 99%
“…Pelagic fishes, such as Pacific herring Clupea pallasii, capelin Mal lo tus villosus, Pacific sandlance Ammodytes hexapterus and eulachon Thaleichthys pacificus, may spawn in Alaska from March through August. The exact timing of spawning in Glacier Bay is not well established for most species (Robards et al 2003, Arimitsu et al 2008), but capelin have been observed spawning in Glacier Bay during June and July (Robards et al 2003).…”
Section: Activity Budgetsmentioning
confidence: 99%
“…Pelagic fishes, such as Pacific herring Clupea pallasii, capelin Mal lo tus villosus, Pacific sandlance Ammodytes hexapterus and eulachon Thaleichthys pacificus, may spawn in Alaska from March through August. The exact timing of spawning in Glacier Bay is not well established for most species (Robards et al 2003, Arimitsu et al 2008), but capelin have been observed spawning in Glacier Bay during June and July (Robards et al 2003).Thus, during spring through at least part of the summer, the combination of a better diet and more time hauled out appears to result in net energy expenditures for glacial seals that are similar to those of terrestrial seals. Dietary differences between habitats became less pronounced as differences in prey quality diminished, or pelagic prey became less available to seals as a result of increased competition from other piscivorous predators that seasonally use the area (Herre man et al 2009a).…”
mentioning
confidence: 99%